Atlas of the Patellofemoral Joint - Sanchis-Alfonso, Vicente (Springer London : Imprint: Springer, 2013)
The Atlas of the Patellofemoral Joint is designed to be a detailed visual guide, presenting the reader with a wealth of images that will act as a crucial aid when faced with surgery of the knee and particularly that of the patella. All the images, footnotes and summaries are compiled in order to convey a simple understanding of this complex problem. It is a very practical book, aimed not only to those that already specialize in knee surgery, but also to the general orthopedic surgeon who wishes to learn more about this particular form of surgery.